The true tails of Baker and Taylor : the library cats who left their pawprints on a small town --and the world - Louch, Jan; Rogak, Lisa, 1962- (Thomas Dunne Books, St. Martin's Press, 2016)
It all started with mice in the library.... Assistant librarian Jan Louch and a coworker decided that what the Minden, Nevada library needed was a cat. They found a pair of Scottish Folds who were perfect for the job. Jan named them Baker and Taylor, and they took up residence in the library. After Jan let the cats be photographed for a poster, they became feline celebrities, and became the most famous library cats in the world.